2022
DOI: 10.1177/03000605221088558
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab therapy for persistent high-grade fever in systemic lupus erythematosus: two cases and a literature review

Abstract: Tocilizumab (TCZ) is a humanized immunoglobulin (Ig) G1 monoclonal antibody directed against the interleukin (IL)-6 receptor. We report on two patients with persistent high-grade fever and systemic lupus erythematosus (SLE) who were treated with TCZ. Two female Chinese patients presented with SLE and high-grade fever, with raised inflammatory markers including C-reactive protein, erythrocyte sedimentation rate, and IL-6, but no signs of opportunistic infections. Their fever and other symptoms responded poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has also been used in an adolescent patient with SLE and a pleural effusion [173]. It was also used successfully in SLE patients with persistent high grade fever and who were resistant to treatment with antibiotics and corticosteroids [174]. Tocilizumab administration has been shown to have beneficial effects in lupus patients with arthritis [175].…”
Section: Interleukin Inhibitors 431 Tocilizumabmentioning
confidence: 99%
“…It has also been used in an adolescent patient with SLE and a pleural effusion [173]. It was also used successfully in SLE patients with persistent high grade fever and who were resistant to treatment with antibiotics and corticosteroids [174]. Tocilizumab administration has been shown to have beneficial effects in lupus patients with arthritis [175].…”
Section: Interleukin Inhibitors 431 Tocilizumabmentioning
confidence: 99%
“…Tocilizumab is currently in Phase I clinical trials for SLE (Table S3). Preliminary data have shown that tocilizumab may be a good alternative treatment for patients with SLE who do not respond to high-dose glucocorticoids, but further studies are needed [131,132].…”
Section: Common Therapeutics For Sle Ssc and Ramentioning
confidence: 99%
“…It has also been used in an adolescent patient with SLE and a pleural effusion [172]. It has also been used successfully in SLE patients with persistent high grade fever, resistant to treatment with antibiotics and corticosteroids [173]. Tocilizumab administration has been shown to have beneficial effects in lupus patients with arthritis [174].…”
Section: Tocilizumabmentioning
confidence: 99%